PENILAIAN KONDISI DAN PREDIKSI SISA UMUR JEMBATAN TAKKALASI DENGAN METODE BRIDGE CONDITION RATING - Hasmar Halim; Pusvita Dhyan Reza Billa; Basyar Bustam; Andi Maal Latief (Politeknik Negeri Semarang, 2025)
This study assesses the structural condition and predicts the remaining service life of the vital Takkalasi Bridge in South Sulawesi, using a systematic Bridge Condition Rating (BCR) method adapted from NYSDOT guidelines. The approach combines geometric data and visual inspections, weighting structural elements to determine a condition value (CR) used for lifespan prediction. Results show the Permanent Reinforced Concrete (LTP) section has a BCR of 4.85 (medium category), requiring rehabilitation with an estimated 21 years remaining service life. The older Australian Steel Frame (RBA) section scored a BCR of 5.07 (good category), needing only regular maintenance with 24 years remaining. This indicates the LTP, though younger, degrades faster due to traffic and environmental exposure, while the consistently maintained RBA performs better. The study confirms BCR as an effective basis for targeted bridge management, maintenance, and rehabilitation planning.